Microwave-Assisted Copper-Powder-Catalyzed Coupling and Cyclization of β-Bromo-α,β-unsaturated Carboxylic Acids with 1,3-Diketones Leading to 2H-Pyran-2-ones - Ho, Son Long; Cho, Chan Sik; Sohn, Ho-Sang (Synthesis, 2015)
β-Bromo-α,β-unsaturated carboxylic acids were coupled and cyclized with 1,3-diketones by microwave irradiation in the presence of a catalytic amount of copper powder and base to give the corresponding 2H-pyran-2-ones in good to high yields.
Keywords: copper; coupling; cyclization; heterocycles; heterogeneous catalysis